2014
DOI: 10.1111/pai.12244
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotics in the first week of life is a risk factor for allergic rhinitis at school age

Abstract: BackgroundHeredity as well as external factors influences the development of allergic rhinitis. The aim of this study was to analyse early risk factors and protective factors for allergic rhinitis at school age.MethodsThis is a prospective, longitudinal study of children born in western Sweden in 2003 where 50% of the birth cohort was randomly selected. The parents answered questionnaires at 6 months, 12 months, 4.5 yr and 8 yr. At 8 yr, 5044 questionnaires were distributed. Of these, 4051 responded, that is, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
42
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(51 citation statements)
references
References 30 publications
6
42
0
2
Order By: Relevance
“…. Furthermore, a prospective study of Swedish children revealed that antibiotics during the first week of life increased the risk of developing allergic rhinitis by 8 years of age while living on a farm during childhood was protective …”
Section: Other Allergies: Allergic Rhinitis Atopic Dermatitis and Ementioning
confidence: 99%
“…. Furthermore, a prospective study of Swedish children revealed that antibiotics during the first week of life increased the risk of developing allergic rhinitis by 8 years of age while living on a farm during childhood was protective …”
Section: Other Allergies: Allergic Rhinitis Atopic Dermatitis and Ementioning
confidence: 99%
“…Only 11 of 34 studies included explicitly reported that the use of antibiotics preceded the diagnosis of allergies. 10,12,16,18,21,[25][26][27]37,38,43 In our meta-analysis, we tested the association between antibiotics and risk of hay fever and eczema only in these 11 studies to infer causality and the results still showed a significant association.…”
Section: -56mentioning
confidence: 99%
“…[61][62][63] İlaç (ateş düşürücü ve antibiyotik) kullanımı: İlk yaşta sık (ayda bir) parasetamol kullanımı ve süt çocuğunda yılda dört kere veya fazla antibiyotik kullanımı AR riskini artırmaktadır. [64] Elli ülke, 113 merkezde, 322.959 ergende yapılan çalışmada asetaminofen kullanımının rino-konjonktivit riskini artırdığı gösterilmiştir. [65] Çocukluk çağı aşıları: Çocukluk çağı viral aşı-larının (DTP, kızamık, suçiçeği ve MMR vb.)…”
Section: çOcukluk çAğı Enfeksiyonlarıunclassified